Off-licence prescribing and regulation in psychiatry: current challenges require a new model of governance. (August 2013) - Sugarman, Philip; Mitchell, Amy; Frogley, Catherine; Dickens, Geoffrey L; Picchioni, Marco
The growing worldwide use of pharmaceuticals is managed in some countries by a regulatory system which sharply divides legal use into licensed and unlicensed categories. We examine how for the range of psychotropics this simultaneously restricts the possible benefits to patients, prescribers and producers in some domains, while failing to manage the risks in others. A more flexible system, which shares at an earlier stage experience and evidence on benefits and risks in patients, previously marginalized on the grounds of age, diagnosis or comorbidity, would aid the development of safer, more effective 'real-world prescribing'. Practical recommendations are made for a new model of research and prescribing governance, to enable more effective repurposing of these treatments.